UPAYA MENINGKATKAN HASIL BELAJAR BAHASA INGGRIS MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER KELAS VIII.5 SMP NEGERI 16 PALEMBANG - Sari, Eka Maya (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
This research is based on the problem: How to improve the learning outcomes of English after the implementation of the class VIII.5 Numbered Head Together (NHT) cooperative learning model in Palembang State Middle School 16? While the purpose of this study is: to find out the improvement of learning outcomes in English after the implementation of the cooperative learning model Numbered Head Together (NHT) class VIII.5 Palembang State Middle School 16. This study uses action research as many as three rounds. Each round consists of four stages, namely: design, activity and observation, reflection, and revision. The target of this study was class VIII.5 Palembang State Middle School 16 with a total of 35 students. The data obtained in the form of formative test results, observation sheets of teaching and learning activities. From the results of the analysis, it was found that students' learning achievement increased from cycle I to cycle III, namely, cycle I (62.86%), cycle II (80.00%) and cycle III (91.43%). The conclusion of this study is that the cooperative learning model Numbered Head Together (NHT) can have a positive effect on the learning outcomes of Palembang State Middle School 16 Students and this learning model can be used as an alternative to learning English.